Polyunsaturated fatty acid enrichment by complexation with silver ion - Huong, Lai Mai (Vietnam Journal of Chemistry, 2014)
The extraction of methyl esters of tuna oil has been performed, and the extraction behavior is discussed. The effects of AgNO3concentration, the addition of water-soluble polar solvents such as methanol to aqueous silver nitrate solutions and the presence of organic solvent on the recovery yield of PUFA-ME have been also investigated. Results show that docosahexaenoic acid methyl ester (DHA-ME) and eicosapetaenoic acid methyl ester (EPA-ME)  and can be selectively extracted into silver nitrate solutions.